Encoding Performance of Orthogonal Space-Time Coded Continuous Phase Modulation System - Wenli Shen (Institute of Advanced Engineering and Science, 2013)
The orthogonal space-time coded continuous phase modulation (OST-CPM) system shows attractive performance over fading MIMO channels. In this paper, the Chernoff bound on pair-wise error probability (PWEP) is studied for two transmit antennas over spatially correlated quasi-static Rayleigh-fading channel. The maximum likelihood sequence detection (MLSD) algorithm is applied to the OST-CPM system. Approximate bound for high signal-to-noise ratio (SNR) is derived to evaluate the encoding performance in correlated channel. The effects of correlation coefficient matrices on the coding performance are simulated. Both analytical and simulation results show that the coding performance of this system decreases as the fading coefficients between the antennas increases. And the penalty on the coding performance increases a lot in fully correlated channel. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2469